2003
DOI: 10.1152/ajprenal.00032.2003
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium transport and pH regulation by K+-Cl-cotransporters

Abstract: The Na(+)-K(+)-Cl(-) cotransporters (NKCCs), which belong to the cation-Cl(-) cotransporter (CCC) family, are able to translocate NH4(+) across cell membranes. In this study, we have used the oocyte expression system to determine whether the K(+)-Cl(-) cotransporters (KCCs) can also transport NH4(+) and whether they play a role in pH regulation. Our results demonstrate that all of the CCCs examined (NKCC1, NKCC2, KCC1, KCC3, and KCC4) can promote NH4(+) translocation, presumably through binding of the ion at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 53 publications
2
82
1
Order By: Relevance
“…NH 4 ϩ is readily transported by a range of K ϩ transporting mechanisms (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), whereas NH 3 , probably due to its resemblance to water, appears to cross cell membranes by facilitated diffusion through a range of aquaporins, among which we here propose that AQP4 is featured. The cerebral glutamate-glutamine cycle encompasses vesicular release of glutamate from the presynapse with subsequent astrocytic uptake, amidation of glutamate to glutamine (a process requiring free ammonia), shuttling of glutamine to the neuronal structures, and its hydrolyzation to glutamate and ammonia.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…NH 4 ϩ is readily transported by a range of K ϩ transporting mechanisms (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), whereas NH 3 , probably due to its resemblance to water, appears to cross cell membranes by facilitated diffusion through a range of aquaporins, among which we here propose that AQP4 is featured. The cerebral glutamate-glutamine cycle encompasses vesicular release of glutamate from the presynapse with subsequent astrocytic uptake, amidation of glutamate to glutamine (a process requiring free ammonia), shuttling of glutamine to the neuronal structures, and its hydrolyzation to glutamate and ammonia.…”
Section: Discussionmentioning
confidence: 75%
“…At physiological pH, its pK a of 9.25 dictates that ϳ1.5% of the ammonia is found as NH 3 , whereas the rest exists as NH 4 ϩ , the latter of which absolutely requires membrane transporters or channels to cross the plasma membrane. Although dedicated NH 4 ϩ transport proteins have been identified (6), NH 4 ϩ is, due to its resemblance to K ϩ , in addition transported by a range of K ϩ transporters and channels, such as the Na ϩ /K ϩ -ATPase, the Na ϩ /K ϩ /2Cl Ϫ cotransporter, the K ϩ /Cl Ϫ cotransporter, and inwardly rectifying, voltage-, and Ca 2ϩ -activated K ϩ channels (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The permeability of NH 4 ϩ through K ϩ channels usually amounts to ϳ10 -20% of the permeability of K ϩ (7).…”
mentioning
confidence: 99%
“…Interestingly it has been reported that KCC1, KCC2, and KCC3 are inhibited at pH Ͻ7.5 when these are expressed in Xenopus oocytes, whereas KCC4 is activated at acidic pH (44). This finding suggests that KCC4 may be specialized to operate in an acidic environment.…”
Section: Discussionmentioning
confidence: 96%
“…Characterization of the Basolateral NH 4 ϩ -transporting Mechanisms-To date, several transporters are known to transport NH 4 ϩ , in particular via K ϩ binding sites (19). Therefore, we characterized the basolateral NH 4 ϩ -transporting activities of NHNE cells.…”
Section: Nhmentioning
confidence: 99%